NFkB and MMP-13 expression in condylar cartilage of temporomandibular joint with occlusal disharmony in vivo - Suhartini; Narmada, Ida Bagus; Hamzah, Zahreni; Joewarini, Endang (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Temporomandibular disorder (TMD) is a collection of symptoms that causes pain and disturbs a person's life quality. One of the trigger factors is mechanical overloading. Mechanical overloading in occlusal disharmony conditions will lead to an inflammatory reaction in the temporomandibular joint (TMJ). This condition will induce nuclear factor Kappa Beta (NFkB) activation to transcribe proinflammatory cytokines and matrix metalloproteinase-13 (MMP13) and will also degrade condylar cartilage as a major factor in strengthening the TMJ. Purpose: The aim of this study was to analyze the expression of NFkB and MMP13 in the condylar cartilage of TMJ with occlusal disharmony. Methods: This research was an experimental study with post-test-only control group design. Twenty Rats (Rattus norvegicus) were divided into four groups: One control group without any intervention and three experimental groups. Occlusal-reducing intervention was due on the right molar of the experimental groups, which were divided into the 7th, 14th, and 21st days. Immunohistochemical staining was performed to determine the expression of NFkB and MMP13 in the condylar cartilage. The data were analyzed by using the Welch test and independent t-test. Results: There were significant differences in NFkB and MMP13 expression between the control and experiment experimental groups (p<0.05). NFkB expression increased on the 7th, 14th, and 21st days of observation. The MMP13 expression showed a significant difference between the control and experimental groups (p<0.05). Conclusion: Occlusal disharmony increases NFkB and MMP13 expression and could affect TMJ integrity and induce TMD. These findings are important for describing the mechanism of TMJ damage and developing potential alternative therapies to prevent further TMD.